Faktor yang Mempengaruhi Sikap dan Niat Warga Negara Indonesia untuk Menggunakan Open Government Data - Sephia Ayu Permatasari; Diah Hari Suryaningrum (Journal of Management and Bussines (JOMB), 2023)
This study aims to examine the influence of eight factors on citizens' attitudes towards open government and government 2.0 and whether these attitudes affect their intention to use Open Government Data in Indonesia. The research method used is a quantitative method with primary data sources obtained from distributing questionnaires. The results of this study indicate that three factors, namely ease of use, usability, and internet competence, have an influence on citizens' attitudes towards open government and government 2.0, and these attitudes affect citizens' intentions to use Open Government Data (OGD). The conclusion is that the attitudes and intentions of citizens towards open government and government 2.0, and attitudes also influence citizens' intentions to use Open Government Data (OGD). Keywords: Data, Public Value, Open Government; Inhabitant